Sepsis in the XXI Century: Etiology, Risk Factors, Epidemiological Features, Complications, Prevention - L. I. Gomanova; A. Y. Brazhnikov (Эпидемиология и вакцинопрофилактика)
Relevance. Sepsis is a life-threatening organ dysfunction caused by dysregulation of the body's response to infection. It is estimated that the annual number of sepsis cases worldwide could be 48 million. An increase in the role of nosocomial infections, an increase in concomitant pathology, and the rapid development of complications lead to negative dynamics in the sepsis incidence and mortality.Aims. Review of the epidemiological characteristics of sepsis in the world and the Russian Federation, study of the etiology, risk factors, complications and prevention of sepsis.Conclusions. The data obtained indicate that sepsis remains an unsolved public health problem in many countries of the world. According to modern data, the annual sepsis (ICD-10: A00-B99, A30-A49, A41) incidence among the adult population in accordance with «Sepsis-3» is 838 per 100 ths. So, assessing the incidence of sepsis and mortality from it, we can identify the negative dynamics of recent years, which is typical for the United States of America, Europe and Asia. For example, the incidence of all forms of sepsis ranges from 25 per 100 ths in Italy (2006) to 883 per 100 ths in Sweden (2019). Moreover, every fourth case of sepsis (24.4%) in the world was acquired during a stay in an ICU. Hospital mortality from all forms of sepsis in various countries ranged from 17.5% in Spain (2013) to 46.3% as a whole and 64.5% with admission to ICU in Brazil (2006–2015). Unfortunately, in the Russian Federation, there are no large studies aimed at assessing sepsis incidence and mortality. According to the results of studies conducted on the basis of ICU in hospitals of St. Petersburg, sepsis incidence was 35 per 100 ICU patients (2006–2007) and 15 per 100 ICU patients (2015). When studying the epidemiological features of sepsis, the following difficulties can be identified: changing the criteria for diagnosing sepsis, comparing data on sepsis, severe sepsis and septic shock, evaluating data on community-acquired and in-hospital sepsis. So, sepsis prevention plays an important role in the public health of many countries. Major preventive strategies to reduce sepsis incidence include raising awareness of sepsis; identification of persons at risk; early diagnosis of sepsis; treatment of comorbid pathology leading to the potential development of sepsis and progression of its complications. The epidemiological status continues to deteriorate due to the growth of antibioticresistant strains, an increase in the proportion of fungal agents, late antibiotic therapy, an unfavorable comorbid status and other factors. Early diagnosis and timely clinical management of sepsis play the main role in the improvement in the quality of life. For example, treatment of chronic infectious diseases, minimization of manageable risk factors, and development of population screening programs will further reduce sepsis incidence and mortality.